2009
DOI: 10.1007/s10689-009-9259-3
|View full text |Cite
|
Sign up to set email alerts
|

Strategies for endometrial screening in the Lynch syndrome population: a patient acceptability study

Abstract: Lynch syndrome is an autosomal dominant syndrome accounting for 2-5% of all colorectal cancer. In addition, women with Lynch syndrome have a substantially increased risk of developing endometrial cancer particularly pre-menopausally when symptom detection is more difficult. Current recommendations are that screening for endometrial cancer be offered to women identified to be at risk. The aim of the study was to assess the relative patient acceptability of the available screening modalities. A survey of the per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…However, as far as we know, there is no information about the degree of pain as well as the influence of pain scores on clinical decision-making during surveillance in women with LS. Only one study reported on patient acceptability of endometrial sampling in LS surveillance and the authors conclude that transvaginal ultrasonography is associated with less discomfort than hysteroscopy or endometrial sampling, and will therefore be the preferred test of choice for the majority [15]. There is no significant difference between the pain scores for hysteroscopy and endometrial sampling [15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, as far as we know, there is no information about the degree of pain as well as the influence of pain scores on clinical decision-making during surveillance in women with LS. Only one study reported on patient acceptability of endometrial sampling in LS surveillance and the authors conclude that transvaginal ultrasonography is associated with less discomfort than hysteroscopy or endometrial sampling, and will therefore be the preferred test of choice for the majority [15]. There is no significant difference between the pain scores for hysteroscopy and endometrial sampling [15].…”
Section: Discussionmentioning
confidence: 99%
“…Only one study reported on patient acceptability of endometrial sampling in LS surveillance and the authors conclude that transvaginal ultrasonography is associated with less discomfort than hysteroscopy or endometrial sampling, and will therefore be the preferred test of choice for the majority [15]. There is no significant difference between the pain scores for hysteroscopy and endometrial sampling [15]. In studies reporting on preventive surgery in women with LS no information is given so far about the influence of pain during the surveillance visits in making the decision for preventive surgery [16, 17].…”
Section: Discussionmentioning
confidence: 99%
“…Elmasry et al 58 assessed the patient acceptability of the available screening modalities. Transvaginal ultrasound was associated with less discomfort than hysteroscopy or Pipelle biopsy.…”
Section: Question Nomentioning
confidence: 99%
“…A recent study evaluating acceptability of screening, found no significant difference in pain scores between either hysteroscopy or endometrial sampling. [30] The efficacy and patient acceptability of OHES is similar to the in-patient procedure and the former is more cost-effective. [31,32] Preliminary data suggest that hysteroscopy-based endometrial screening in LS does not appear to be associated with any psychological morbidity.…”
Section: Discussionmentioning
confidence: 99%